The Concept of Teleology in Kant, Hegel, and Marx - Clayton Jr., Eugene (Con-Textos Kantianos. International Journal of Philosophy, 2023)
Breaking with Aristotle’s Physics, Kant effects a theoretical reconception of teleology. It is this paper’s contention that the truth of the Kantian conception of teleology as ‘a purposiveness of nature in behalf of our faculty for cognizing it’ is not that of being a solution to Hume’s problem of induction or the condition for the possibility of subjective cognition of the empirical, but that it is a theoretical means of the subjective domination over the objective. A materialist reading of Hegel’s criticism of Kant’s antinomy of teleological judgment in the Science of Logic is then proposed. Finally, the non-teleological nature of capital is demonstrated.